Generational change in fruit and vegetable consumption in Mexico through an age-period-cohort analysis 1994-2014 - López González, Fabiola (2017)
Objective: To quantify the change in the consumption of fruits and vegetables in Mexico between 1994 and 2014, to identify its trend over time and to segment the group of households by level of consumption, according to the age of the head of household, with the intention of understanding the evolution of the consumption of fruits and vegetables of the Mexican population. Material and methods: Data on fruit and vegetable expenditure from the National Household Income and Expenditure Survey were used from 1994 to 2014; An F-test on per capita consumption was performed to identify if the increase was significant and the age-cohort-period modeling of this variable was carried out to anticipate long-term changes. Results: Fruit and vegetable purchase habits between 1994 and 2014 reflect an increase of 60 grams (30.3%) in the consumption of these foods in the period of observation. We found age-cohort-period effects, and a positive relation between the consumption of fruits and vegetables and age. Conclusions: Consumption of fruits and vegetables increased significantly during the studied period; this rising is expected to continue as a result of population aging. It is necessary to increase the consumption of these foods in young people in order to prevent the development of chronic diseases.